Interstitial lung disease incidence and mortality in the UK and the European Union: an observational study, 2001–2017. Issue 3 (11th July 2022) - Salciccioli, Justin D.; Marshall, Dominic C.; Goodall, Richard; Crowley, Conor; Shalhoub, Joseph; Patel, Preya; Molyneaux, Philip L.
Objective: To compare the trends in age-standardised incidence and mortality from interstitial lung diseases (ILD) in the UK and the European Union (EU). Methods: This was an observational study using data obtained from the Global Burden of Disease Study on residents of the UK and of the 27 EU countries. The main outcome measures were ILD age-standardised incidence rates per 100 000 (ASIR), age-standardised death rates per 100 000 (ASDR) and mortality-to-incidence ratios (MIRs), which are presented for men and women separately for each country for the years 2001–2017. Trends were analysed using joinpoint regression analysis. Results: In 2017, the median incidence of ILD was 7.22 (IQR 5.57–8.96) per 100 000 population for men and 4.34 (IQR 3.36–6.29) per 100 000 population for women. In 2017, the median ASDR attributed to ILD was 2.04 (IQR 1.13–2.71) per 100 000 population for men and 1.02 (0.68–1.37) per 100 000 population for women. There was an overall increase in ASDR during the observation period, with a median increase of +20.42% (IQR 5.44–31.40) for men and +15.44% (IQR −1.01–31.52) for women. Despite increases in mortality over the entire observation period, there were decreasing mortality trends in the majority of countries at the end of the observation period (75% for men and 86% for women). Conclusion: Over the past two decades, there have been increases in the incidence and mortality of ILD in Europe. The most recent trends, however, demonstrate decreases in mortality from ILD in the majority of European countries for both men and women. These data support the ongoing improvements in the diagnosis and management of ILD. Recent improvements in the diagnosis and management of interstitial lung disease, as well as the introduction of therapeutic agents, have resulted in significant decreases in mortality in the majority of European countries https://bit.ly/3JHkEyO